2018
DOI: 10.1007/s13197-018-3103-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant and probiotics characterization of dominant bacterial isolates from traditional fermented fish of Manipur, North-East India

Abstract: -, and are traditional fermented fish products produced by the Manipuri people living in the North-Eastern part of India. The present study was designed with the aim to isolate, identify and characterize the microorganisms present in these fermented foods. Bacterial pure cultures were isolated using serially diluted samples and were further identified by conventional biochemical tests and Sanger sequencing of 16s rRNA gene. Results show that the number of bacterial count in Nutrient agar and Starch casein agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Higher DPPH radical scavenging activity reveals the high contents of antioxidants in the fermented fish products. These results are supported with the reports made by some others researchers [5,13]. It is well recognized that the bioactive agents from our diet can inhibit the effects caused by oxidative stress [17].…”
Section: Ph Total Volatile Base Nitrogen (Tvb-n) Content and Dpph Radical Scavenging Activity (%)supporting
confidence: 91%
See 1 more Smart Citation
“…Higher DPPH radical scavenging activity reveals the high contents of antioxidants in the fermented fish products. These results are supported with the reports made by some others researchers [5,13]. It is well recognized that the bioactive agents from our diet can inhibit the effects caused by oxidative stress [17].…”
Section: Ph Total Volatile Base Nitrogen (Tvb-n) Content and Dpph Radical Scavenging Activity (%)supporting
confidence: 91%
“…Indigenous people in this region use native fermented fish products to provide the basic components of their diet, with various features of nutrition, flavor, palatability and texture [2]. Enhanced flavor, digestibility and therapeutic value have been reported in fermented fish products with improved nutritional and functional properties [3][4][5][6]. Consumption of fermented fishes introduces and balances beneficial bacteria into the digestive tract for higher nutrients absorption of the nutrients by regulating enough digestive enzymes [7].…”
Section: Introductionmentioning
confidence: 99%
“…The process of traditional fermentation is generally spontaneous, triggered by microorganisms associated with the raw food materials and the external environment (Misihairabgwi and Cheikhyoussef, 2017). The unique structure of the microbiota in each fermented food described in previous studies has confirmed the microbial activity and medicinal value of fermented food products (Singh et al, 2018). Therefore, this research on the microbial diversity of fermented seafood explores the treasure trove of unique microbial resources in Hainan Province.…”
Section: Introductionsupporting
confidence: 75%
“…has been reported from Utonga-kupsu, Hentak, and Ngari (traditional fermented fish of Manipur, North-East India) alongside Staphylococcus. These have also been reported from other fermented fish products such as Namplaa and Kapi (from Thailand) and have been shown to exhibit amylase, protease, and cellulase activities that can improve the quantity, availability, and digestibility of dietary nutrients in the body in addition to other probiotic effects [65,83]. S. simulans PMRS35 isolated from budu, a traditional Thai salt-fermented fish-based product, possessed high lipase and protease activities and a vast array of desirable probiotic characteristics [70].…”
Section: Probiotics From Fermented Fishmentioning
confidence: 53%